Assessments of an Innovative Fertilizer Management Tool (Nutrient Expert®) for Improved Nutrient Management of Spring Maize at Rani Jamara Kulariya Irrigation Command Area of Tikapur, Kailali - Amgain, Lal P.; Pandey, Prem; Neupane, Sushil; Bhattarai, Basanta Raj; Mahatra, Jay B. (Journal of the Institute of Agriculture and Animal Science, 2023)
A multi-locational field trials were assessed to know the innovative fertilizer management tool (Nutrient Expert®) for improved nutrient management of Spring Maize in Rani Jamara Kulariya Irrigation Project Command Area (RJKIPCA) of Tikapur, Kailali during spring season of 2021. The layout and planting of Spring Maize for NE® - Hybrid Maize model for 42 farmers’ fields (Tikapur-18, Janaki-18 and Lamkichuha-6)], and Nutrient Omission Plot Technique (NOPT) maize trials for 21 farmers’ fields (Tikapur-9, Janaki-9 and Lamkichuha-3) were grown using baby trail/ diamond trials in Randomized Complete Block Design (RCBD) considering farmers as replications. Data recording, tabulation, and analysis and interpretation of the data was performed by using ANOVA through the use of R Stat-software. Data analysis was also done for the yield gap analysis using percentage change in yield of Spring Maize over the location due to changes in crop cultivars and NOPT. The experimental results highlighted that most of the soils in the project site were deficit in N followed by K, with the minimum yield loss due to omission of P. The treatment; farmers' fertilizer practices (FFP) with their own cultivar has shown more decreasing trend in Spring Maize yields and it was more prominently seen within the farmers growing hybrid maize than the open pollinated variety (OPV). With huge percentage of yield gaps in Spring Maize denoted that the soil of Janaki and Tikapur were found to be more prone to N and K nutrients deficient than the soils of Lamkichuha. NE®- Hybrid Maize model has fairly predicted the Spring Maize yields and predicted the sound results on profitability with assured actual attainable yield over the FFP. Therefore, NE-model for Spring Maize is suggested to adopt as a recommended decision support system (DSS) tool in the project command areas of RJKIPCA, Tikapur, Kailali.